Comparison of HIV-1 genotypic resistance test interpretation systems in predicting virological outcomes over time - Frentz, Dineke (2013)
Several decision support systems have been developed to interpret HIV-1 drug resistance genotyping results. This study compares the ability of the most commonly used systems (ANRS, Rega, and Stanford's HIVdb) to predict virological outcome at 12, 24, and 48 weeks.